KAJIAN ARSITEKTUR BERLAPIS UNTUK PENGEMBANGAN APLIKASI DALAM MENDUKUNG PEMBANGUNAN APLIKASI DI PEMERINTAHAN PROVINSI JAWA BARAT - Ramdhani, Taufik Iqbal (Badan Penelitian dan Pengembangan Daerah Provinsi Jawa Barat, 2024)
The Electronic-Based Government System (EBGS) includes regulations for application development in the context of digital transformation to enhance public services. However, the increasing innovation in the government sector faces challenges in governing and standardizing application development technology, especially for specific applications in the West Java Provincial Government. The gap between technology selection and human resource planning can lead to an excessive number of applications without optimizing maintenance and development. Therefore, this study emphasizes the importance of technology standardization in application development to support the government's digital transformation. The study presents a four-layer technology architecture design: front-end, middleware, back-end, and persistent. The classification of technology standards is divided into three levels: small, medium, and large, based on the number of users, transactions, and data. By standardizing, it is expected to increase the efficiency and effectiveness of application development, reduce development costs, increase team productivity, and optimize application quality. This study also highlights the relevance of implementing this architecture in the West Java Provincial Government environment, with reference to existing local regulations and policies. The results of the study indicate that this four-layer technology standardization can be an effective solution to overcome the challenges of government application development and support sustainable digital transformation